HOW PEER PRESSURE AFFECTS THE CONFORMITY OF ADOLESCENTS IN CHOOSINGTHEIR HOBBIES AND INTERESTS IN UZBEKISTAN? (World Economics and Finance Bulletin, 2024)
The focus of this paper is to examine the peer pressure on adolescents in Uzbekistan, through investigating that specific aspect of their life being theinterests and hobbies they choose to take up. An adolescent is an individual who is mostly affected by other people’s opinions more so those of their peers. What makes it worse in Uzbekistan where deep-rooted beliefs exist but change is beingcourted, the issue of peer pressure is further enhanced by cultural norms. The research included 108 adolescents, and employed the modified Peer Pressure Scale Questionnaire-Revised (PPSQ-r) in the collection of such data. The data reveals that a sizable proportion of the adolescents under study were peerpressurized in areas affecting their performance in academics, social behavior and even in their choice of leisure activities.